2018
DOI: 10.1038/s41598-018-28353-6
|View full text |Cite
|
Sign up to set email alerts
|

Stepwise Reduction of Graphene Oxide (GO) and Its Effects on Chemical and Colloidal Properties

Abstract: Graphene Oxides (GO) typically contains different oxygen containing groups such as hydroxyl, carboxyl and epoxy, and reduced GO (r-GO) represents a family of material with diverse chemical properties. In an effort to understand how properties of r-GO change as GO is reduced, a stepwise reduction of the same GO to r-GO containing different levels of oxygen was carried out, and their corresponding chemical and colloidal properties are reported. Starting with GO containing 49 percent oxygen, r-GOs containing 31, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(53 citation statements)
references
References 39 publications
(41 reference statements)
2
50
0
Order By: Relevance
“…The electrochemical reduction of GO through cyclic voltammetry was chosen to control the extent of reduction of the GO. We measured the IR absorption spectra of the starting GO and the resulting rGO ( Figure S1 ), which confirmed that the number of oxygen-containing functional groups, such as C–O (1060 cm −1 ), C–OH (1226 cm −1 ), and C=O (1733 cm −1 ) [ 39 ], decreased as the GO is electrochemically reduced. Moreover, we checked the electrode active surface area of the GO- and rGO-modified electrode using a standard solution of 5 mM Fe(CN) 6 3+ containing 0.1 M KCl.…”
Section: Resultsmentioning
confidence: 70%
“…The electrochemical reduction of GO through cyclic voltammetry was chosen to control the extent of reduction of the GO. We measured the IR absorption spectra of the starting GO and the resulting rGO ( Figure S1 ), which confirmed that the number of oxygen-containing functional groups, such as C–O (1060 cm −1 ), C–OH (1226 cm −1 ), and C=O (1733 cm −1 ) [ 39 ], decreased as the GO is electrochemically reduced. Moreover, we checked the electrode active surface area of the GO- and rGO-modified electrode using a standard solution of 5 mM Fe(CN) 6 3+ containing 0.1 M KCl.…”
Section: Resultsmentioning
confidence: 70%
“…rGO, on the other hand, is prepared from rGO by thermal, chemical, or electrical treatments. Hence there are always some defects resulting from unreduced O 2 functional groups in or on the rGO surface, and subsequently, rGO cannot have the perfect graphene structure, which was described above [267].…”
Section: Graphene and Graphene Derivativesmentioning
confidence: 98%
“…They used nanosized graphene oxide (NGO) to cover AgNPs (Ag@NGO). Two‐dimensional NGO is inert, which saves NPs from oxidation and allows light to pass easily . These properties of NGO make it suitable for use as a protective layer on AgNPs as a SERS substrate.…”
Section: Sers‐based Biosensorsmentioning
confidence: 99%
“…[126] They used nanosized graphene oxide (NGO) to cover AgNPs (Ag@NGO).T wo-dimensional NGO is inert, which saves NPs from oxidationa nd allows light to pass easily. [127] These properties of NGO make it suitable for use as ap rotective layer on AgNPs as aS ERS substrate. The Raman spectra of NGO and Ag@NGO showedt hat the Da nd Gb ands of NGO were intensified after attachment of AgNPs; this is ascribed to the sharp SPR of AgNP.T he Raman spectra of HepG-2 cancer cells without the Ag@NGO substrate displayed no band duet o the low scattering intensity of cell components.…”
Section: Silver Nps As As Ers Biosensormentioning
confidence: 99%